Successful Treatment of Multiplex Alopecia Areata Using Transactional Analysis: A Case Report - Takashi Yamakita; Yoshinori Shimizu; Masaru Arima; Mutsumi Ashihara; Kayoko Matsunaga (Karger Publishers, 2014)
The patient was a 13-year-old female. Six years previously, she developed alopecia areata when her parents divorced. One year after that, the bald area drastically expanded when her mother remarried. She was treated at her local hospital; however, no improvement was observed. She then visited our hospital for examination. A bald patch was covering >80% of her head. Self Grow-Up Egogram indicated the basic interpersonal relationship stance of 'I am not OK, You are OK'. We therefore implemented a transactional analysis approach to increase the patient's score on the Free Child subscale. New hair growth was observed after 6 months and the bald patch disappeared after 2 years. Our results suggest that this method could also be easily applied in a clinical setting by dermatologists.